15. 70° because a right angle is 90° and we have the angle of ADB which is 20°. So 90°-20°=70°.
16. 70° because angle PSQ is 60° and angle QSR is 10°. So 60°+10°=70°.
17. 55° because it says it in the explanation. I assume this is a typo and they meant to ask the measurement of ADC and in that case it would be 130° because angle ADB is 75° and angle BDC is 55°. 75°+55°=130°.
18. 40° because angle PSQ is a right angle which means it's 90°. So 130°-90°=40°.
19. 140° because angle ADB is 120° and angle BDC is 20° so 120°+20°=140°.
20. 125° because again it's in the explanation. But if it's a typo and they meant what is the measurement of PSQ then it is 50° because PSR is 125° and QSR is 75° so 125°-75°=50°.
Hope this helps! :)
Answer:
Tom’s age is 7 years
Mary’s age is 13 years
Step-by-step explanation:
Since we do not know the ages, let’s represent the ages by variables at first.
Let m represent mary’s age will t represent Tom’s age.
Now, let’s proceed to have equations.
Adding square of Tom’s age (t^2) to mary’s age give 62
t^2 + m = 62 •••••••(i)
Adding square of mary’s age (m^2) to Tom’s age give 176
m^2 + t = 176 •••••••(ii)
Now, to get the individual ages, we will need to solve both equations simultaneously.
Solving both equations simultaneously without mathematical softwares can be a little hard.
By the use of mathematical software ( wolfram alpha to be specific), we can input both equations and allow the software to solve.
By inputing these equations, we have the values of t to be 7 and m to be 13
And if we try to check by inspection, we can see that these values are actually correct.
7^2 + 13 = 62
13^2 + 7 = 176
Answer:
The Graph Shifts 4 units up
Step-by-step explanation:
Okay so, when you add four to a graph in this manner we have to look at the equation as a whole. f(x)=mx+b + 4. By adding four we are changing the y-intercept and shifting it up four. This will cause the entire graph to shift upwards four spaces.
Answer:
Step-by-step explanation:
abc = 1
We have to prove that,
![\frac{1}{1+a+b^{-1}}+\frac{1}{1+b+c^{-1}}+\frac{1}{1+c+a^{-1}}=1](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B1%2Ba%2Bb%5E%7B-1%7D%7D%2B%5Cfrac%7B1%7D%7B1%2Bb%2Bc%5E%7B-1%7D%7D%2B%5Cfrac%7B1%7D%7B1%2Bc%2Ba%5E%7B-1%7D%7D%3D1)
We take left hand side of the given equation and solve it,
![\frac{1}{1+a+\frac{1}{b}}+\frac{1}{1+b+\frac{1}{c}}+\frac{1}{1+c+\frac{1}{a}}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B1%2Ba%2B%5Cfrac%7B1%7D%7Bb%7D%7D%2B%5Cfrac%7B1%7D%7B1%2Bb%2B%5Cfrac%7B1%7D%7Bc%7D%7D%2B%5Cfrac%7B1%7D%7B1%2Bc%2B%5Cfrac%7B1%7D%7Ba%7D%7D)
Since, abc = 1,
and c = ![\frac{1}{ab}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bab%7D)
By substituting these values in the expression,
![\frac{1}{1+a+\frac{1}{b}}+\frac{1}{1+b+\frac{1}{c}}+\frac{1}{1+c+\frac{1}{a}}=\frac{1}{1+a+\frac{1}{b}}+\frac{1}{1+b+ab}+\frac{1}{1+\frac{1}{ab}+\frac{1}{a}}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B1%2Ba%2B%5Cfrac%7B1%7D%7Bb%7D%7D%2B%5Cfrac%7B1%7D%7B1%2Bb%2B%5Cfrac%7B1%7D%7Bc%7D%7D%2B%5Cfrac%7B1%7D%7B1%2Bc%2B%5Cfrac%7B1%7D%7Ba%7D%7D%3D%5Cfrac%7B1%7D%7B1%2Ba%2B%5Cfrac%7B1%7D%7Bb%7D%7D%2B%5Cfrac%7B1%7D%7B1%2Bb%2Bab%7D%2B%5Cfrac%7B1%7D%7B1%2B%5Cfrac%7B1%7D%7Bab%7D%2B%5Cfrac%7B1%7D%7Ba%7D%7D)
![=\frac{b}{b+ab+1}+\frac{1}{1+b+ab}+\frac{ab}{ab+1+b}](https://tex.z-dn.net/?f=%3D%5Cfrac%7Bb%7D%7Bb%2Bab%2B1%7D%2B%5Cfrac%7B1%7D%7B1%2Bb%2Bab%7D%2B%5Cfrac%7Bab%7D%7Bab%2B1%2Bb%7D)
![=\frac{1+b+ab}{1+b+ab}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B1%2Bb%2Bab%7D%7B1%2Bb%2Bab%7D)
![=1](https://tex.z-dn.net/?f=%3D1)
Which equal to the right hand side of the equation.
Hence, ![\frac{1}{1+a+b^{-1}}+\frac{1}{1+b+c^{-1}}+\frac{1}{1+c+a^{-1}}=1](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B1%2Ba%2Bb%5E%7B-1%7D%7D%2B%5Cfrac%7B1%7D%7B1%2Bb%2Bc%5E%7B-1%7D%7D%2B%5Cfrac%7B1%7D%7B1%2Bc%2Ba%5E%7B-1%7D%7D%3D1)
D) 34/5 because 6(5) = 30 30+4=34 , so its 34/5